Electroreduction of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid: Oriented product selectivity through the electrode material. (20th April 2018) - Michez, Roman; Vander Steen, Julien; Doneux, Thomas; Luhmer, Michel; Buess-Herman, Claudine
Abstract: A new insight into the electrochemical reduction mechanism of imidazolium cations is given by examining the cathodic stability of the 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [BMIm][NTf2 ] ionic liquid at platinum, gold, copper and mercury electrodes. Potentiostatic electrolyses were performed under nitrogen-saturated conditions and the major reduction products of the BMIm + cation were quantified by 1 H NMR spectroscopy. The product selectivity is influenced by the electrode material and by the presence of an additional proton source in the medium, evidencing the key role of adsorbed hydrogen in the mechanism of BMIm + electroreduction.